Enhancing soybean yields with plant growth-promoting rhizobacteria - Abdulkareem1, Yusuf Folorunsho; Aliyu, Olawale Mashood (Annals of Bangladesh Agriculture, 2025)
Soybean is a vital legume crop renowned for its high protein (42%) and oil (19.5%) contents. Despite its nutritional and economic significance, soybean production in Africa remains low. This study evaluated the effects of rhizobium inoculation rates (0, 0.5, 0.75, and 1.0 g per 10 g seeds) on yields of five soybean varieties (Sam soy-2, TGX-1448-2E, TGX-1479, Local, and TGX-1740) under field condition at National Center for Agricultural Mechanization (NCAM), Idofian and screenhouse conditions at Kwara State University, Malete in southern Guinea savannah environment of Nigeria. The two experiment (field and screen house) were laid out in a 5 x 4 split-plot arrangement fitted into randomized complete block design for the field and the screenhouse experiment was arranged in a complete randomized design with three replications. Results showed that Rhizobium inoculation significantly improved yield components, including nodulation, pod weight, seed weight, and hundred-seed weight, with the highest performance observed at 1.0 g inoculant rate. TGX-1479 exhibited superior yield traits in the field, while TGX-1740-1E performed the best in the screenhouse. Environmental factors influenced field performance more than genetic variation, whereas genetic composition dominated in the screenhouse. The study concludes that utilization of rhizobium inoculation at 1.0 g per 10 g seeds is a strategy to enhance soybean productivity, recommending TGX-1479 and TGX-1740-1E for optimal yields in the tropical agroecology. These findings might support sustainable soybean production to improve food security in the resource-limited regions. Ann. Bangladesh Agric. 29(1): 1-12